The Use of Crossword Puzzle towards the Students Vocabulary - Nurteteng Nurteteng; Dewi Nopitasari (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2019)
Vocabulary is an important one of the language components that should be learnt by students, so they can master the English well. This research is conducted to know the student vocabulary improving after taught using crossword puzzles. The research used pre-experimental design which is need an experimental class. The sample of this research is the first grade of SMAN 5 Makassar which consist of 20 students. In collecting the data, the researcher used vocabulary test that has administered in pretest and posttest. The result showed that the mean score in posttest was 76.75 that is higher than the mean score in pre-test was 55.5. The score of t-test was 0.02 was smaller than α (0.05). It can be said that using puzzles can improve the students’ vocabulary mastery.